ANALISIS PENGARUH PUBLIC RELATION TERHADAP CUSTOMER LOYALTY YANG DIMODERASI OLEH BRAND IMAGE PADA SMARTPHONE â€Xâ€ - Suhaily, Lily; Elias, Elias (Fakultas Ekonomi, UIN Maliki Malang, 2014)
Development of technology today is higly increased, especially communication tecnology. Basedon this fenomenon, many companies have opportunity to build-up smartphone. This conditions will increasedcompetition between the company. To win the competitions, company must promote their smartphone byusing public relation. According that conditions, this research evaluate the influence of public relation tocustomer loyalty which moderated by brand image. 160 questionnares were distributed to on 26 Mei 2014untill 1 July 2014by using random sampling.The result shows that public relation influences customer loyaltywhich moderated by brand image